Evolutionary Genetics - Maynard Smith, John (Oxford University Press, 1998)
This second edition of John Maynard Smith's text on population biology, genetics and biological anthropology, includes new research findings on game theory and a new chapter on molecular genetics and the reconstruction of evolutionary history.